Quinolone Prophylaxis in Transrectal Ultrasound Guided Prostate Biopsy: An Eight-Year Single Center Experience - Bing-Juin Chiang; Yeong Shiau Pu; Shiu-Dong Chung; Shih-Ping Liu; Hong-Jeng Yu; Shuo-Meng Wang; Hong-Chiang Chang; I-Ni Chiang; Chao-Yuan Huang (The Scientific World Journal)
We retrospectively evaluated the efficacy of prophylaxis with pipemidic acid and levofloxacin in transrectal ultrasound guided prostate biopsy (TRUSP-Bx). From January 2002 to December 2004, patients receiving oral pipemidic acid 500 mg twice daily for three days with or without a preoperative intravenous cefazolin 1 gm injection comprised group A. Between January 2005 and December 2009, patients receiving oral levofloxacin 500 mg one hour before biopsy comprised group B. We calculated the annual febrile urinary tract infection (fUTI) rates. Patients’ characteristics, including age, prophylactic antibiotics, biopsy core numbers, pathologic results, PSA, and the spectrums and susceptibility of pathogens, were also evaluated. A total of 1313 (35.5%) patients belonged to group A, while 2381 (64.5%) patients belonged to group B. Seventy-three patients experienced postoperative infectious complications. There was a significant difference in the fUTI rate between groups A and B (3.7% versus 1.0%, P<0.001). The yearly fUTI rates varied from 0.6 to 3.9% between 2002 and 2009. Of the 73 patients with fUTI, those receiving levofloxacin prophylaxis were more likely to harbor fluoroquinolone-resistant pathogens (P<0.001). E. coli was the most common pathogen in both groups. Levofloxacin remains effective and appears superior to pipemidic acid based prophylaxis.